Autologous Stem-Cell-Based Gene Therapy for Inherited Disorders: State of the Art and Perspectives - Staal, Frank J. T.; Aiuti, Alessandro; Cavazzana, Marina (Frontiers in Pediatrics, 2019)
Gene therapy using patient-derived stem cells is rapidly becoming an alternative to allogeneic stem cell transplantation, especially when suitable compatible donors cannot be found. Efficient viral delivery methods for therapeutic genes have allowed the development of genetic medicines for inherited disorders of the immune system, hemoglobinopathies and various devastating metabolic diseases. Here we briefly review the state of the art developments in the field, including gene editing approaches. Concluding, an increasing number of paediatric indications can be successfully cured by hematopoietic stem cell based gene therapy.